1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Proof of the Fundamental Theorem of Calculus.

  1. Mar 16, 2013 #1
    Hi all I'm currently working my way through proving the FToC by proving something that is a foundation for it. So I need to prove that;

    L(f,P[itex]_{1}[/itex]) ≥ L(f,P) where P[itex]\subset[/itex]P[itex]_{1}[/itex] i.e where P[itex]_{1}[/itex] is a refinement of P.

    So, Let P[itex]_{1}[/itex] = P [itex]\cup[/itex] {c} where c [itex]\in[/itex] [x[itex]_{k-1}[/itex],x[itex]_{k}[/itex]]

    Let L' = inf{x|x [itex]\in[/itex] [x[itex]_{k-1}[/itex],c]}

    Let L'' = inf{x|x[itex]\in[/itex]} [c,x[itex]_{k}[/itex]]

    L = inf{x|x[itex]\in[/itex] [x[itex]_{k-1}[/itex],x[itex]_{k}[/itex]]}

    So from this the next line is;

    L'(c-x[itex]_{k-1}[/itex]) + L''(x[itex]_{k}[/itex]-c) ≥ L(x[itex]_{k}[/itex]-x[itex]_{k-1}[/itex])

    Now this is the line I can't fully grasp. How was this line come up with? I can understand it from a geometrical/graphical/pictorial point of view, but from an analytic point of view I cannot.

    So far this is what I have,

    L' + L'' ≥ L

    And If I multiply by the differences in the x-ordinates I still don't get the same line. Any help would be appreciated.

    How exactly did that mystery line happen?
  2. jcsd
  3. Mar 16, 2013 #2
    I know what you mean, but I'm going to comment on your notation anyway.

    If you want to use LaTeX, then you should not just use LaTeX on each individual symbol, but rather on the whole line. So writing something like

    Code (Text):

    L(f,P,[itеx]_{1}[/itеx]) ≥ L(f,P)
    it is much handier (and much more aesthetic) to write

    Code (Text):

    [itеx]L(f,P_1)\geq L(f,P)[itеx]
    As you wrote it now, we have that ##L^\prime = x_{k-1}##. You should probably have written

    [tex]L^\prime = inf \{ f(x)~\vert~x \in [x_{k-1},c]\}[/tex]

    Same remark with the others.

    As it is now, it is simply not true. Take [itex]f(x)=-1[/itex] and take [itex]x_k=0[/itex], ##c=1## and ##x_{k+1}=2##. Then ##L = L^\prime = L^{\prime\prime} = -1##. But

    [tex]L^\prime + L^{\prime\prime} = -2 \leq -1 = L[/tex]
  4. Mar 16, 2013 #3
    [itex]L^{'}[/itex]([itex]c-x_{k-1}[/itex]) = [itex](-1)[/itex][itex](1-2)[/itex] = 1

    [itex]L^{''}[/itex]([itex]x_{k}-c[/itex]) = (-1)(0-1) = 1

    [itex]L[/itex] = [itex](-1)[/itex][itex](x_{k}-[/itex][itex]x_{k-1}[/itex]) = -1(-2) = 2

    [itex]1 + 1 ≥ 2[/itex]

    Does it not hold?
  5. Mar 16, 2013 #4
    Oh, you meant that ##L(x_k - x_{k-1})## is a multiplication. I thought it was part of the notation. Makes sense then.

    Here's a hint to prove it

    [tex]L(x_k - x_{k-1}) = L(x_k-c) + L(c-x_{k-1})[/tex]
  6. Mar 16, 2013 #5
    [itex]L(x_{k}-x_{k-1})[/itex] = [itex]L(x_{k}-c)[/itex] + [itex]L(c-x_{k-1})[/itex]

    [itex]L ≤ L'[/itex] and [itex]L ≤ L''[/itex]

    [itex]\Rightarrow[/itex] [itex]L(x_{k}-x_{k-1})[/itex] ≤ [itex]L''(x_{k}-c)[/itex] + [itex]L'(c-x_{k-1})[/itex]

    This correct?
  7. Mar 16, 2013 #6
    Yes. Be sure that you know how to prove ##L\leq L^\prime## though.
  8. Mar 16, 2013 #7
    Hmm, that I don't know but i'll attempt it later and get back to you on it if I don't get it. Thanks for the help! Super as always!

    BTW, would this be the kind of exercise one would expect from Spivak?
  9. Mar 16, 2013 #8
    Yes. This is more of an exercise you would encounter in Spivak than in another calculus book. Those exercises tend to be difficult at first, but you get used to them pretty quickly.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted